THE EFFECTIVENESS OF MEDIA REMBUK PEKON IN PREVENTING CONFLICT IN PEKON WAY SULUH KRUI SELATAN PESISIR BARAT LAMPUNG - Yanzi, Hermi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
This research attempts to examined the effectiveness of media rembuk pekon as prevention conflict in Pekon Way Suluh Krui Selatan Pesisir Barat Lampung. Practically as a input for the local government and society for mutual operate rembuk pekon as conflict prevention, the termination of conflict, in order to keep social harmonisation good in solving problems in the society. This research using qualitative descriptive method with the subject of research pekon officials, society personage, custom personage, and the youth. Collected data technique is interview guidelines to be supported by guidelines observation and documentation. While analysis data using the credibility with triangulation. This research result indicates media of rembuk pekon very effective help people prevention, termination, and recovery post conflict in the societies, able to mediate in the resolution of social problems such as fights, misunderstand, a vigilante, immoral, theft, and defamation. In conclusion that the media rembuk pekon is effective as the media in the solution of social problems that happens in society. Suggestion in ask is internally media rembuk pekon in society with the role of social institutions such as pekon officials, society personage, custom personage, and the youth.